2003
DOI: 10.1152/ajpcell.00058.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for normal splenic T lymphocyte functions in proestrus females after trauma: enhanced local synthesis of 17β-estradiol

Abstract: and resuscitation (TH) produces profound immunodepression and enhances susceptibility to sepsis in males but not in proestrus females, suggesting gender dimorphism in the immune responses. However, the mechanism responsible for the maintenance of immune functions in proestrus females after TH is unclear. Splenic T lymphocytes express receptors for estrogen (ER), contain enzymes involved in estrogen metabolism, and are the major source of cytokine production; the metabolism of 17␤-estradiol was assessed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 60 publications
0
25
1
Order By: Relevance
“…Both ERα and ERβ are detected in murine splenic T cells [8]. However, ERβ expression has been found markedly lower than ERα [8] or present only in some Tcell subsets [4], which may explain the difference between our findings and those of Harrington et al [46] in transfected HEC-1 cells.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Both ERα and ERβ are detected in murine splenic T cells [8]. However, ERβ expression has been found markedly lower than ERα [8] or present only in some Tcell subsets [4], which may explain the difference between our findings and those of Harrington et al [46] in transfected HEC-1 cells.…”
Section: Discussioncontrasting
confidence: 74%
“…ERs are classified into two distinct subtypes-ERα and ERβ [2]. Both subtypes have been detected in thymus [3][4][5][6], bone marrow [7] and spleen [5,8]. The wide distribution of ERα and ERβ in the immune system implies their specific roles in mediating the immunomodulatory actions of estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…Following trauma, the expression of ER-β was significantly different in OVX mice; specifically it was decreased in proestrus mice but increased in OVX mice. Therefore, down-regulation of ER-β may then change expression of cytokines by T cells in these mice [112]. Other studies have suggested a spatial difference in immune-regulation by the two receptors with respect to tissue.…”
Section: Mechanisms Sectionmentioning
confidence: 89%
“…36 Androgens may act on telomerase expression in hematopoietic tissue after conversion in peripheral tissues to metabolites, such as 17␤-estradiol and 5␣-dihydrotestosterone; leukocytes express aromatase (CYP19), the enzyme responsible for aromatization of the testosterone A ring by conversion to 17␤-estradiol ( Figure 3E). 23,24,37 Androgens increased low baseline telomerase activity in individuals carrying a loss-of-function TERT mutation to normal levels (Table 3). These results have direct implications for patients with aplastic anemia carrying telomerase complex mutations and in dyskeratosis congenita, potentially explaining the effectiveness of male hormones in these syndromes, as well as guiding what type of androgenic compounds (readily aromatized) or even estrogens may be even more effective in the future.…”
Section: Discussionmentioning
confidence: 99%